The Influence of Learning Style and Learning Motivation on Student Learning Outcomes in Science Subjects Natural and Social - Winarno, Kukuh; Muharramsyah, Rambang; Rahmi Novalita, Rahmi Novalita (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
This research aims to describe; a) The influence of learning styles on student learning outcomes in Natural and Social Sciences subjects, b) The influence of learning motivation on student learning outcomes in Natural and Social Sciences subjects, c) The influence of learning styles and learning motivation on student learning outcomes in subjects Social Science and Natural Sciences lessons. This type of research is quantitative research. The population and sample in this study were all 72 students in grades IV, V, VI of the Negri 15 Linge Elementary School, Central Aceh Regency. Data collection techniques use observation, questionnaires and documentation. Data analysis techniques use multiple linear regression test analysis. The research results show that; a) there is a significant influence of learning style on student learning outcomes in Natural and Social Sciences subjects, where the Sig. for the (partial) influence of learning style on learning outcomes is 0.00 < 0.05 and the calculated t value is 5.210 > 1.994 so it can be concluded that H1 is accepted which means there is an influence of learning style (X1) on Learning Outcomes (Y). b) There is a significant influence between learning motivation on student learning outcomes in Natural and Social Sciences subjects, where the Sig. for the (partial) influence of learning motivation on learning outcomes is 0.00 < 0.05 and the calculated t value is 3,199 > 1.99 so it can be concluded that H2 is accepted, which means there is an influence of learning motivation (X2) on learning outcomes (Y), c) There is a significant influence of learning style and learning motivation on student learning outcomes in Social Sciences and Natural Sciences subjects where, the Sig. for the (simultaneous) influence of learning style and learning motivation on learning outcomes is 0.00 < 0.05 and the calculated F value is 44.06> 3.13 so it can be concluded that H3 is accepted which means there is an influence of Learning Style (X1) and Learning Motivation ( X2) simultaneously on Learning Outcomes (Y)